(untitled) (Nepal Journal of Health Sciences, 2022)
Maxillary canines affect the smile and facial esthetics providing upper lip and alar base support. This article presents the case report of skeletal class I malocclusion with Angle’s class III (Right) subdivision and impacted left maxillary canine of poor prognosis for traction which was managed successfully with a combined surgical and orthodontic approach. The diagnosis of the impaction was done through the Orthopantogram, intra-oral periapical, and occlusal radiographs and was localized buccally through clinical examination and Clark’s technique. The impacted canine was brought into the arch which improved the smile and self-esteem of the patient.